Sex and species recognition by wild male southern white rhinoceros using contact pant calls - Cinková, Ivana; Policht, Richard (Animal cognition, 2016)
Recognition of information from acoustic signals is crucial in many animals, and individuals are under selection pressure to discriminate between the signals of conspecifics and heterospecifics or males and females. Here, we first report that rhinos use information encoded in their calls to assess conspecifics and individuals of closely related species. The southern (Ceratotherium simum) and critically endangered northern (C. cottoni) white rhinos are the most social out of all the rhinoceros species and use a contact call pant. We found that southern white rhino pant calls provide reliable information about the caller's sex, age class and social situation. Playback experiments on wild territorial southern white rhinoceros males revealed that they responded more strongly to the pant calls of conspecific females compared to the calls of other territorial males. This suggests that pant calls are more important form of communication between males and females than between territorial males. Territorial southern males also discriminated between female and territorial male calls of northern species and reacted more intensively to the calls of northern than southern males. This might be caused by a novelty effect since both species naturally live in allopatry. We conclude that white rhinos can directly benefit from assessing individuals at long distances using vocal cues especially because their eyesight is poor. Pant calls thus likely play a significant role in their social relationships and spatial organization. In addition, better understanding of vocal communication in white rhinos might be helpful in conservation management particularly because of their low reproduction in captivity.
Keywords: Discrimination, Psychological; Vocalization, Animal; Sex Characteristics; zvířata; druhová specificita; mužské pohlaví; Age Factors; Species Specificity; diskriminace (psychologie); Perissodactyla; ženské pohlaví; věkové faktory; Animals; teritorialita; Territoriality; vokalizace zvířat; pohlavní dimorfismus; Male; Female